Polyethylene glycol solutions rapidly restore and maintain axonal continuity, neuromuscular structures, and behaviors lost after sciatic nerve transections in female rats. Issue 7 (16th April 2018) - Mikesh, Michelle; Ghergherehchi, Cameron L.; Hastings, Robert Louis; Ali, Amir; Rahesh, Sina; Jagannath, Karthik; Sengelaub, Dale R.; Trevino, Richard C.; Jackson, David M.; Bittner, George D.
Abstract: Complete severance of major peripheral mixed sensory–motor nerve proximally in a mammalian limb produces immediate loss of action potential conduction and voluntary behaviors mediated by the severed distal axonal segments. These severed distal segments undergo Wallerian degeneration within days. Denervated muscles atrophy within weeks. Slowly regenerating (∼1 mm/day) outgrowths from surviving proximal stumps that often nonspecifically reinnervate denervated targets produce poor, if any, restoration of lost voluntary behaviors. In contrast, in this study using completely transected female rat sciatic axons as a model system, we provide extensive morphometric, immunohistochemical, electrophysiological, and behavioral data to show that these adverse outcomes are avoided by microsuturing closely apposed axonal cut ends (neurorrhaphy) and applying a sequence of well‐specified solutions, one of which contains polyethylene glycol (PEG). This "PEG‐fusion" procedure within minutes reestablishes axoplasmic and axolemmal continuity and signaling by nonspecifically fusing (connecting) closely apposed open ends of severed motor and/or sensory axons at the lesion site. These PEG‐fused axons continue to conduct action potentials and generate muscle action potentials and muscle twitches for months and do not undergo Wallerian degeneration. Continuously innervated muscle fibers undergo much less atrophy compared with denervated muscle fibers. Dramatic behavioral recovery to near‐unoperated levels occurs within days to weeks, almost certainly by activating many central nervous system and peripheral nervous system synaptic and other plasticities, some perhaps to a greater extent than most neuroscientists would expect. Negative control transections in which neurorrhaphy and all solutions except the PEG‐containing solution are applied produce none of these remarkably fortuitous outcomes observed for PEG‐fusion. Abstract : Soleus neuromuscular junctions 7 days after a complete sciatic transection with PEG‐fusion (PEG) or gold standard microsuture repair (‐PEG). PEG‐fusion repair maintains nerves (arrow) and neuromuscular function and restores near‐normal voluntary behavior within weeks.